Structural and Optical Properties of R6G Doped Nanotitania Thin Films Deposited via Sol–Gel Dip-coating Meth - Saeed, Muhammad A.; Ameen, Majida A. (Sulaimani Journal for Pure and Applied Sciences, 2022)
Pure and rhodamine 6G (R6G) doped titanium dioxide (TiO2) nanostructure thin films with different concentrations (310-4 , 310-5 , 310-6 , and 310-7 ) M of doped TiO2 sol were deposited on glass substrate via dip-coated sol-gel method. Amorphous structure of the pure and doped TiO2 thin films was identified by X-ray diffraction (XRD) technique. UV-Visible (UV-vis) and fluorescence spectrophotometry techniques were used to study optical and spectroscopic characterization of the samples, respectively. The absorption spectra for all pure and doped TiO2 films indicate a strong absorbance in the UV region which open the possible application of these films for UV filter optical element. 50 nm blue shift of the absorption edge for the TiO2 films with respect to the sol was observed which proves the nanostructure texture of TiO2 thin films. Upon increasing dye concentration, a red shift in the maximum fluorescence emission peaks of R6G ethanolic solution and doped TiO2 sol was observed. The presence of R6G dye molecules in the matrix of TiO2 films is demonstrated by the appearance of two distinct intensity fluorescence peaks at 540 and 600 nm. Various fluorescence peaks of R6G doped TiO2 thin films were observed in UV-vis region under 300 nm pumping wavelength.
Keywords: Nanostructure TiO2 thin films; R6G dye; dip-coated sol-gel; fluorescence emission spectrum